The effect of different forms of selenium on fatty acid composition in broiler meat - Hiranon, N.; Sivapirunthep, P.; Chaosap, C. (My University, 2018)
The effects of selenium (Se) in diets on fatty acid composition, lipid indices, and enzyme indexes for desaturase, elongase, and thioesterase in Pectoralis muscle of broiler chicken were investigated. A total of 360 one-day-old chicks (Arbor Acres) were randomly assigned to 2 treatments with 6 replicates, giving 30 birds per replicate. The birds were fed ad libitum in 3 feed phases of giving 2 dietary treatments comprised 0.3 ppm of inorganic Se from sodium selenite (Na-Se) and 0.3 ppm of organic Se from Zn-L-selenomethionine (Zn-L-SeMet). At 39 days of age, one bird from each treatment was randomly selected and slaughtered. Pectoralis muscles were collected and stored at -40 °C before fatty acid composition analysis. There were not significantly different between organic and inorganic selenium treatment on fatty acid composition, lipid indices, and enzyme indexes (P>0.05). However, the results demonstrated that Zn-L-SeMet had slightly lower I/A (6.7%) while had higher h/H (4.4%) and MUFA (8%) than Na-Se.
Keywords: Broiler chicken; Fatty acid composition; Forms of selenium